PENEMPATAN BAK SAMPAH ORGANIK, ANORGANIK, DAN B3 DENGAN KONSEP GO GREEN PERUMAHAN BUDI AGUNG RW 03/RT 05 - Mohamad Nurul Fiqih; Syaiful Syaiful; Renea Shinta Aminda (JPMUJ, 2023)
Garbage is the residue of human daily activities and/or from natural processes in solid form. The purpose of the output in this research is to invite local people to care about the environment by sorting waste and utilizing waste that can be managed. the method in carrying out this research uses a method of randomly interviewing residents and conducting a questionnaire test. Recycle trash with 3R: reduce, reuse, recycle.